(untitled) (Global Journal of Management and Business Research, 2013)
The paper critically investigated poverty in Nigeria over the years, considering its persistent rise in spite of various measures instituted by different Nigerian leaders. The study revealed that improper identification of the poor, lack of adequate monitoring of programmes, corruption, inconsistent policies, poor funding of programmes, lack of industries, poor infrastructure and irregular power supply, among others, have contributed significantly meteoric rise in poverty over the years. Among the ways forward articulated are: proper research and survey are required before commencement of programmes; sufficient monitoring and consistency in policies are essential; intensification of modernized agricultural practices in Nigeria; annihilation of corruption in all levels through leaders’ change of attitude; and mass participation of citizens in policy formulation and service delivery are imperative now.